Design and Construction Pond Temperature Control System and Automatic Nile Tilapia Fish Feeder for Aquaponics - Putri Yeni Aisyah; Dyah Ayu Permadani (Institut Teknologi Sepuluh Nopember, 2022)
Expansion of land for the development of human civilization reduces natural ecosystems. Especially land for agriculture and fisheries in densely populated areas. The more the population, the more food needs. One way to deal with this problem is aquaponic cultivation. Aquaponics is a modern practical farming system that integrates plant cultivation systems with aquatic animal cultivation. In aquaponics cultivation there are factors that need to be considered. One of these success factors is the Temperature and Automatic Feeder in the pond. To get the temperature needed by the fish, temperature control is carried out using the DS18B20 sensor. When the fish pond temperature drops below 28°C, the heater will automatically turn on to raise the pond temperature, and when the pond temperature rises above 32°C, the peltier will turn on and start lowering the pond temperature. Feeding is one of the success factors for aquaponics. If the feed given does not match the weight and age of the fish, the growth of the fish can be disrupted, causing the fish to die. Automatic feeding uses the RTC module as the set time and the servo motor as the opening valve for the fish feed container. Fish were fed at 08.00, 12.00, and 17.00. The average error obtained after validating the DS18B20 sensor is 0.61. The accuracy obtained is 98.05%. The ratio of fish RGR before and after the control system was installed was 7.14% and 11.2 The fish FCR values before and after the control system was installed were 12.50% and 21.07%. The plant growth rates before and after the control system was installed were 22.9% and 33.71%.